Entrepreneurship practices as a strategic tool for poverty reduction in Nigeria - Popoola, Mufutau Akanmu; Ojo, Azeez Olasunkanmi; Akande, Shittu Saheed (Management and Entrepreneurship: Trends of Development, 2025)
This study examined the impact of entrepreneurship practices on poverty alleviation and extremely reduction in Nigeria. According to Popoola (2021), High rate of poverty is a threat to our country economic development and this Poverty in any community or society is a serious and highly setback to the economics, socioeconomic, social, and general level of any development of the society. This study revealed four (4) hypotheses to achieve the target set of goals and answer the research questions accordingly. The main objectives are to; (i) examines the real effect of entrepreneurship-practices on skills-acquisitions among beads makers in Nigeria; (ii) to determine the effect of entrepreneurship-practices on income generation's among beads makers in Nigeria; (iii) to evaluate the extent to which entrepreneurship-practice's effect employment-creations among beads makers in our dear country Nigeria; and (iv) to investigate the effect of entrepreneurship practice's on enterprise-creations among beads makers in Nigeria. Data were collected by using questionnaires which were deployed to the real register beads makers in Oyo, Osun and Ogun States respectively. These questionnaires were retrieved with adequate monitoring. Analysis of data by using Chi- Square test was employed to test all the hypothesis to determines effect of entrepreneurship-practice's (measured by mentoring, entrepreneurial-mindset, Creativity and Innovation on poverty reductions (measured by the skill acquisitions, employment creations, income generation's and real enterprise creations scale measurements to determine this on general well being of the populace.The findings revealed that Entrepreneurship practices is an antidote to poverty reduction. It shows positive impact of Entrepreneurship practices on Poverty reduction in Nigeria. The study recommendations that government at various levels should set up skills acquisition centers nationwide and Entrepreneurial mindset curriculum should be introduce to Nigeria educational system in order to boost entrepreneurial mindset of the populace.JEL Classification: L26, O12, I3